Effectiveness of Ibuprofen versus Novafen in Reducing Pain after Molar Extractions: Novafen versus Iboprofen after Molar Extraction - Taghian, Mehdi; Heidari, Mohadeseh; Yazadani, Jamshid; Arian, Tohid; Mollaei, Melika; Tabarestani, Amirreza; Sadri, Leyli (Regeneration, Reconstruction & Restoration (Triple R), 2024)
Background and objectives: Tooth extraction is often associated with pain and discomfort for patients. There are still controversies over the proper painkiller with minimum side effects to be prescribed after extractions. Therefore, the current study aims to compare the pain-relieving effect of Novafen versus Ibuprofen after maxillary and mandibular molar extractions. Materials and methods: The present cohort study consisted of 80 healthy individuals who were candidates for extraction of their molar teeth under local anesthesia. Patients were randomly divided into two groups (N = 40) and were instructed to use Novafen or Ibuprofen, respectively, every 6 hours post-extraction. Pain assessment was conducted using Visual Analogue Scale (VAS). Data analysis was performed using SPSS v25. The Chi square test was performed for qualitative and t-tests for quantitative variables. Pain relief times were compared using Kaplan-Meier curves and Cox regression, with hazard ratios assessing differences between the two drugs. Results: The findings revealed that both medications affected similarly up to 12 hours post-treatment; however, Novafen exhibited a shorter time to pain relief than Ibuprofen after 12 hours. Thus, Novafen demonstrated a significantly faster time to pain relief than Ibuprofen (P < 0.005). Moreover, the hazard ratio for the analgesic effect of Novafen relative to Ibuprofen was 2.55, indicating that Novafen has a shorter time to pain relief than Ibuprofen (P < 0.002). Conclusion: Both Novafen and Ibuprofen are effective in reducing pain after molar extractions; however, Novafen can be a more reliable choice in reducing pain and discomfort.